Surgical treatment of rectal cancer patients aged 80 years and older—a German nationwide analysis comparing short- and long-term survival after laparoscopic and open tumor resection. Issue 9 (September 2019) - Völkel, Vinzenz; Draeger, Teresa; Schnitzbauer, Valentin; Gerken, Michael; Benz, Stefan; Klinkhammer-Schalke, Monika; Fürst, Alois
Abstract: Background: Minimally invasive removal of rectal tumors has proven to be a safe alternative to the open approach. Despite increased use of laparoscopy, its eligibility for older adults requires further exploration. This study compares perioperative mortality and 5-year overall, disease-free, and relative survival after laparoscopic and open surgery in rectal cancer patients aged ≥80 years. Materials and methods: Data derive from 30 German regional cancer registries and cover approximately one quarter of the entire German population. All primary nonmetastatic rectal adenocarcinoma cases with surgery between 2005 and 2014 were eligible for inclusion. To compare survival rates, Kaplan–Meier analysis, a relative survival model, and multivariable Cox regression were applied; a sensitivity analysis assessed bias by exclusion. Results: 1532 patients were included, of whom 17.1% underwent laparoscopic procedures. 30 days after surgery, 2.7% of the laparoscopy patients had died compared to 7.0% in the open surgery group. The multivariable analysis confirmed that minimally invasive procedures are followed by a lower 30-day postoperative mortality risk (odds ratio, OR, 0.352; 95% confidence interval, CI, 0.161–0.771; p  = 0.009). With a 5-year disease-free survival rate of 52.0 vs. 47.6% ( p  = 0.557), only an nonsignificant long-term advantage of the minimally invasive approach was observed. Conclusion: Given the results of this study, older rectal cancer patients are likely to benefit from the laparoscopic approach in the short term, and there are also no disadvantages in terms of long-term survival. Therefore, laparoscopy should be considered a standard procedure for older adults as well.